The regulatory role of m6A in cancer metastasis - Zhou, Ying; Cao, Peng; Zhu, Qing (Frontiers in Cell and Developmental Biology, 2025)
Metastasis remains a primary cause of cancer-related mortality, with its intricate mechanisms continuing to be uncovered through advancing research. Among the various regulatory processes involved, RNA modification has emerged as a critical epitranscriptomic mechanism influencing cancer metastasis. N6-methyladenosine (m6A), recognized as one of the most prevalent and functionally significant RNA modifications, plays a central role in the regulation of RNA metabolism. In this review, we explore the multifaceted role of m6A in the different stages of cancer metastasis, including epithelial–mesenchymal transition, invasion, migration, and colonization. In addition to summarizing the current state of our understanding, we offer insights into how m6A modifications modulate key oncogenic pathways, highlighting the implications of recent discoveries for therapeutic interventions. Furthermore, we critically assess the limitations of previous studies and propose areas for future research, including the potential for targeting m6A as a novel approach in anti-metastatic therapies. Our analysis provides a comprehensive understanding of the regulatory landscape of m6A in metastasis, offering directions for continued exploration in this rapidly evolving field.